2013
DOI: 10.1071/an12426
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differential duodenal gene expression levels and microbiota abundance correlated with differences in energy utilisation in chickens

Abstract: Abstract. Among the terrestrial production animals, chickens are the most efficient users of energy. Apparent metabolisable energy (AME) is a measure of energy utilisation efficiency representing the difference between energy consumed and energy lost via the excreta. There are significant differences in the energy utilisation capability of individual birds that have a similar genetic background and are raised under identical conditions. It would be of benefit to poultry producers if the basis of these differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…When comparing the relative microbiota composition between RFI ranks, separately for females and males, only the Lactobacillus genus and two Lactobacillus crispatus -OTUs in feces were indicative for high RFI in females at both geographical locations. Moreover, the relative abundances of the two Lactobacillus crispatus -OTUs in cecal digesta and feces were also indicative for low TBWG and high FCR values, respectively, again only in females, thereby confirming previous findings [ 30 , 33 ]. Lactobacillus have been shown the ability to activate both innate defense mechanisms and adaptive immune responses in chicken’s intestine [ 29 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When comparing the relative microbiota composition between RFI ranks, separately for females and males, only the Lactobacillus genus and two Lactobacillus crispatus -OTUs in feces were indicative for high RFI in females at both geographical locations. Moreover, the relative abundances of the two Lactobacillus crispatus -OTUs in cecal digesta and feces were also indicative for low TBWG and high FCR values, respectively, again only in females, thereby confirming previous findings [ 30 , 33 ]. Lactobacillus have been shown the ability to activate both innate defense mechanisms and adaptive immune responses in chicken’s intestine [ 29 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 87%
“…Because different selection strategies for FE (e.g. FCR, AME or RFI) were previously applied [ 5 , 7 , 8 , 30 ], this may have contributed to the inter-study variation in FE-associated bacterial taxa. This assumption is supported by findings in cattle where correlations between efficiency parameters and bacterial genera abundances differed depending on the FE metric used (i.e., FCR vs. RFI) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, L. salivarius and Lactobacillus agilis may enhance intestinal butyrate production, which may be beneficial for intestinal health via cross-feeding, as shown for an in vitro-simulated chicken cecum (22). Nevertheless, inconsistent findings were reported for the association between lactobacilli and FE in chickens (7,8,23,24), which may be due to particularities in experimental design, microbiota composition, diet, and the intestinal site investigated. When correlating individual RFI values with bacterial abundances in feces at 29 dph, the results indicated that RFI associations existed with other low-abundance phylotypes (relative abundances of 0.09 to 0.18% at 29 dph).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the latter two studies, bacterial phylotypes related to L. crispatus along with two other Lactobacillus species, were linked to low avian growth performance (Torok et al 2011). Also, Konsak et al (2013) found that an OTU which was most closely related to L.…”
Section: Most Of the Microbiota In Both Dietary Treatments Belonged Tmentioning
confidence: 99%